The Perancangan Prototype Monitoring Area Parkir Mobil Berbasis Internet of Things - Daeli, Erwin Aldin Saputera (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The increasing number of private vehicle users in urban areas is often not balanced with the addition of adequate parking lots, causing significant problems such as congestion and irregular parking control. This study aims to design and implement an Internet of Things (IoT)-based parking area monitoring system that can provide real-time parking availability information via a website. This system uses an ESP32 microcontroller, ultrasonic sensors, and infrared sensors to detect the presence of vehicles in the parking area. This system is expected to make it easier for drivers to find empty parking areas, reduce traffic congestion, and improve travel efficiency. Research methods include literature studies, prototype development experiments, and system performance testing in a controlled environment. The results of this study indicate that the IoT-based parking monitoring system can function well in monitoring parking area availability and providing accurate information to users.